2019
DOI: 10.1109/lwc.2019.2933392
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Network Assisted Approach for Antenna Selection in Untrusted Relay Networks

Abstract: This letter mainly studies the transmit antenna selection(TAS) based on deep learning (DL) scheme in untrusted relay networks. In previous work, we discover that machine learning (ML)-based antenna selection schemes have small performance degradation caused by complicated coupling relationship between achievable secrecy rate and the channel gains. To solve the issue, we here introduce deep neural network (DNN) to decouple the complicated relationship. The simulation results show the DNN scheme can achieve bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A training data set size of M = 10 5 is considered and the SOP is plotted by averaging the results from M = 10 6 batches of test data. The parameters for the traditional ML (SVM, k-NN, and NB) and DNN schemes are the same as those in [9] and [13], respectively. For the LSTM parameters, activation functions for all gates are taken to be sigmoid, whereas the hyperbolic tangent is used for the memory cell in accordance with the standard LSTM architecture [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A training data set size of M = 10 5 is considered and the SOP is plotted by averaging the results from M = 10 6 batches of test data. The parameters for the traditional ML (SVM, k-NN, and NB) and DNN schemes are the same as those in [9] and [13], respectively. For the LSTM parameters, activation functions for all gates are taken to be sigmoid, whereas the hyperbolic tangent is used for the memory cell in accordance with the standard LSTM architecture [18].…”
Section: Resultsmentioning
confidence: 99%
“…DL can handle nonlinear problems and its performance improves with the size of the data, which may not be the case for traditional ML models [12]. The authors in [13] implemented a deep neural network (DNN) scheme for TAS in an untrusted relay network. The authors showed that the DNN performs better than traditional ML schemes and achieves almost the same secrecy rate as the conventional scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Content may change prior to final publication. [175] [163] [167], [176] [177] [178] to help cities plan roads based on the data obtained from road-installed sensors and the data reported from sensor nodes installed in vehicles. Armed with such data, city transport agencies can plan better, and vehicle owners can also reserve parking spots in advance.…”
Section: B Smart Transportmentioning
confidence: 99%
“…For each channel sample, the tag generation is an exhaustive search result of the global optimization design for the joint optimization of relay selection and cooperative beamforming in [28]. Specifically, the label is the index to which relay can achieve the maximum realizable rate under the transmitted power constraints in (6). This process goes on to generate the whole training data set.…”
Section: ) Training Set Preparationmentioning
confidence: 99%
“…Data-driven based joint beamforming, and antenna selection scheme is studied in [5] in which a favorable tradeoff of system performance and computation complexity has been observed. For relay systems, the Transmission Antenna Selection (TAS) scheme is investigated based on data-driven algorithms for entrusted relay networks [6], [7]. Some studies have applied Q-learning to solve the relay selection problem.…”
Section: Introductionmentioning
confidence: 99%